Faktor-Faktor yang Berhubungan dengan Kepuasan Pasien BPJS terhadap Pelayanan Rawat Jalan di Rumah Sakit Panti Wilasa Citarum Semarang - Suryati Suryati; Bagoes Widjanarko; VG Tinoek Istiarti (Jurnal Kesehatan Masyarakat (Undip), 2017)
BPJS is a legal entity established to organize a Health Insurance Program. BPJS success indicator is the people’s satisfaction of hospital services. Complaint patient BPJS about service at hospital Panti Wilasa Citarum Semarang like long service waiting time of drug pharmacy, less spacious parking lot, and the delay of doctor to the practices place. The purpose of this study was to analyze factors related to patient satisfaction with the service outpatients BPJS in Panti Wilasa Citarum Hospital Semarang based on dimension tangible, reliability, responsiveness, assurance, and empathy.This research using descriptive analytic study cross sectional. The population of 371 patients. Sample 77 patients by accidental sampling. Data were analyzed using Chi Square test with α = 0,005. The results showed 57 respondents 74% are satisfied, while as many as 20 respondents 26% are not satisfied. From the stastitical test Chi Square obtained relationships age by patient satisfaction of dimension Empathy ( p value = 0, 035 ), there is a correlation between education and patient satisfaction of the dimensions of Reliability p = 0,007, and no relation between the kind of clinic visits by patient satisfaction of dimensions Reliability p =0,025.This study can be concluded that 74% of patients are satisfied BPJS and factors relating to satisfaction of the patients were age, education, and kind of clinic visits respondent.